Two-Dimensional High-Entropy Metal Phosphorus Trichalcogenides for Enhanced Hydrogen Evolution Reaction - Wang, Ran; Huang, Jinzhen; Zhang, Xinghong; Han, Jiecai; Zhang, Zhihua; Gao, Tangling; Xu, Lingling; Liu, Shengwei; Xu, Ping; Song, Bo (ACS nano, 2022)
Developing earth-abundant and highly effective electrocatalysts for hydrogen evolution reaction (HER) is a prerequisite for the upcoming hydrogen energy society. Two-dimensional (2D) high-entropy metal phosphorus trichalcogenides (MPCh3) have the advantages of both near-continuous adsorption energies of high-entropy alloys (HEAs) and large specific surface area of 2D materials, which are excellent catalytic platforms. As a typical 2D high-entropy catalyst, Co0.6(VMnNiZn)0.4PS3 nanosheets with high-concentration active sites are successfully demonstrated to show enhanced HER performance: an overpotential of 65.9 mV at a current density of 10 mA cm–2 and a Tafel slope of 65.5 mV dec–1. Decent spectroscopy characterizations are combined with density function theory analyses to show the scenario for the enhancement mechanism by a high-entropy strategy. The optimized S sites on the edge and P sites on the basal plane provide more active sites for hydrogen adsorption, and the introduced Mn sites boost water dissociation during the Volmer step. Two-dimensional high-entropy MPCh3 provides an avenue for the combination of HEAs and 2D materials to enhance the HER performance, which also provides an alternative materials platform to explore and design superior catalysts for various electrochemical systems.